2011
DOI: 10.1186/1756-0500-4-408
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive curated resource for follicle stimulating hormone signaling

Abstract: BackgroundFollicle stimulating hormone (FSH) is an important hormone responsible for growth, maturation and function of the human reproductive system. FSH regulates the synthesis of steroid hormones such as estrogen and progesterone, proliferation and maturation of follicles in the ovary and spermatogenesis in the testes. FSH is a glycoprotein heterodimer that binds and acts through the FSH receptor, a G-protein coupled receptor. Although online pathway repositories provide information about G-protein coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…RPS6KB1 is involved in the FSH signaling pathway (Telikicherla et al . ). It has been shown that FSH was elevated in high‐ vs. low‐ovulating females during the pro‐ and peri‐estrous periods in pigs (Knox et al .…”
Section: Discussionmentioning
confidence: 97%
“…RPS6KB1 is involved in the FSH signaling pathway (Telikicherla et al . ). It has been shown that FSH was elevated in high‐ vs. low‐ovulating females during the pro‐ and peri‐estrous periods in pigs (Knox et al .…”
Section: Discussionmentioning
confidence: 97%
“…This is unlikely related to differences in the menstrual cycle stage between baseline and follow up visits, since we carefully scheduled all study visits to occur at the same stage of the menstrual cycle. While we cannot definitively rule out a direct effect of Sm treatment on FSH levels, this pathway shares several of its signaling components with other pathways, and in particular with the mammalian target of rapamycin (mTOR) pathway 46 . In the current study, Sm treatment was also associated with down-regulation of the mTOR pathway (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…The ovarian steroids, 17β‐estradiol (E2) and progesterone (P4), are critical for promoting and maintaining follicle growth, differentiation, maturation and release of a viable oocyte, and formation and regression of the corpus luteum (Chryssikopoulos, ; Mahesh & Brann, ). Ovarian steroidogenesis occurs according to the two‐cell/two‐gonadotropin theory in humans and mice (Telikicherla et al, ). This theory describes how granulosa and theca cells work together to make the ovarian steroids and then induce the maturation of oocytes.…”
Section: Discussionmentioning
confidence: 99%